COMPARISON BETWEEN OLANZAPINE AND HALOPERIDOL AS TREATMENT OF ACUTE AGITATION - Nadlirah, Faizah (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – Antipsychotics have been used as a treatment of choice in acute agitation, with haloperidol being the most widely used from the first generation, and olanzapine from the second generation. Therefore, there is a need to understand these drugs, particularly in their efficacy and safety as a treatment of acute agitation. Methods – This review uses several works of literature between 2011 to 2021 that discuss olanzapine and haloperidol as treatments for acute agitation. Results – Atypical antipsychotic agents are equally effective when compared to typical antipsychotics in treating acute agitation Discuss – On several head-to-head comparisons, olanzapine showed superiority to haloperidol based on the onset of efficacy. Conclusion – Agitated patients interfere with the diagnostic and treatment process. First-line treatment involves verbal de-escalation for patients and if failed, a physician could use pharmacological intervention in the form of rapid tranquillization to continue the therapeutic process. When determining which drug to use, a physician must consider both efficacy and safety. Due to the heterogeneity of study results, it is difficult to conclude that a certain agent is the best treatment for acute agitation. Olanzapine and haloperidol are equally effective antipsychotic agents in treating agitated symptoms. Olanzapine has numerous advantageous properties, including a lesser risk of causing extrapyramidal side effects that in turn can aggravate agitation, but the downside of olanzapine is that it is expensive and has limited availability compared to haloperidol. On the other hand, haloperidol, as a monotherapy or combination therapy either with an antihistamine-anticholinergic or benzodiazepine is a good alternative. Therefore, determining which agent to use should consider the comprehensive state of the patient, as is almost always the case when psychotropic medications are prescribed. Keywords: olanzapine, haloperidol, agitation.